1995
DOI: 10.1007/bf01499323
|View full text |Cite
|
Sign up to set email alerts
|

The MacArthur Treatment Competence Study. III: Abilities of patients to consent to psychiatric and medical treatments.

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.Springer is collaborating with JSTOR to digitize, preserve and extend access to Law and Human Behavior. This article reports the development and psychometric properties of three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
238
1
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 438 publications
(255 citation statements)
references
References 16 publications
14
238
1
2
Order By: Relevance
“…Many physical illnesses, as well as medications, can place patients at risk for impaired understanding of research or treatment Grisso and Appelbaum 1998). In fact, studies comparing the abilities of patients with and without psychiatric illness have shown that the presence of a psychiatric disorder, albeit a risk factor, does not predetermine whether a patient can understand key information Appelbaum et al 1999;Grisso and Appelbaum 1995;Appelbaum and Grisso 1995;Lidz et al 1984;Meisel and Roth 1981;Roth et al 1987;Stanley et al 1987;Sugarman et al 1999;Carpenter et al 2000). Several investigators have demonstrated that individuals with psychiatric disorders do possess definite strengths related to decision-making capacity (Grisso and Appelbaum 1998;Carpenter et al 2000;Kleinman et al 1993;Stanley et al 1981;Soskis 1978).…”
mentioning
confidence: 99%
“…Many physical illnesses, as well as medications, can place patients at risk for impaired understanding of research or treatment Grisso and Appelbaum 1998). In fact, studies comparing the abilities of patients with and without psychiatric illness have shown that the presence of a psychiatric disorder, albeit a risk factor, does not predetermine whether a patient can understand key information Appelbaum et al 1999;Grisso and Appelbaum 1995;Appelbaum and Grisso 1995;Lidz et al 1984;Meisel and Roth 1981;Roth et al 1987;Stanley et al 1987;Sugarman et al 1999;Carpenter et al 2000). Several investigators have demonstrated that individuals with psychiatric disorders do possess definite strengths related to decision-making capacity (Grisso and Appelbaum 1998;Carpenter et al 2000;Kleinman et al 1993;Stanley et al 1981;Soskis 1978).…”
mentioning
confidence: 99%
“…We know from experimental work that people with depression, a prime psychiatric indicator for DBS, appear to be able to "pass" operationalized measures of the three ma jor U.S. tests for competence to consent to treatment (Berg et a!. 1996;Grisso and Appelbaum 1995). In the case of ex perimental DBS, the knowledge base is so thin that there is a strong argument that decision makers should choose the most demanding test, but note that choosing the most demanding increases the level of paternalism.…”
Section: )mentioning
confidence: 99%
“…In 1992, Bonnie (Bonnie, 1992) proposed a theoretical reform of competence parameters for criminal defendants, which was later restructured for clinical application by Grisso (Grisso & Appelbaum, 1995), as the MacArthur Assessment Test. This test analyzes four functional domains: 1) Capacity to communicate a choice; 2) Understand the Relevant Information; 3) Appreciate the situation and its consequences, and 4) Reasons about offered options.…”
Section: The Choice Of Tests To Analyze Capacitymentioning
confidence: 99%